HUBUNGAN VARIASI AKSES KAMPANYE MEDIA SOSIAL TERHADAP BUDAYA POLITIK GENERASI Z PADA ISU PEMILU 2024 - Azifah; Sari, Maya Mustika Kartika (Kajian Moral dan Kewarganegaraan, 2024)
Access variation means that the entry point to access on social media is mainly used as a political campaign platform by candidate pairs that can influence the political culture of generation Z including cognitive, affective and evaluative so that it can influence the political choices that will be used in the Election. This study aims to determine the relationship between variations in social media campaign access and the political culture of generation Z on the issue of the 2024 election. The population in this study was all generation Z in Sidoarjo Regency with the Quota Sampling method which took 6 respondents from each sub-district in Sidoarjo so that 108 samples were obtained. The data analysis method used Spearman correlation analysis with prerequisite tests in the form of normality and linearity tests. The results of this study are that there is a positive and significant relationship between variations in access to the political culture of generation Z Sidoarjo with a Spearman correlation value of 0.542 and generation Z data which is classified as sufficient with a percentage of 33%. So it can be concluded that the higher the variation of access, the higher the political culture owned, so the type of political culture owned by generation Z Sidoarjo in its role in accessing social media political campaign issues is also included in a mixed political culture, namely a semi-participatory political culture of the people. In addition, generation Z is quite active in expressing their preferences for candidate pairs through access to social media political campaigns, but they do not involve various issues too much in interfering with political decisions that will be used in the Election